Method for repairing concrete cracks at low temperature and its application and concrete crack repairing agent
Through the incomplete condensation of the multimer of the POSS structure of the stool type, the problem of failure of the early strength agent in the low temperature environment is solved, and the early strength improvement and repair effect improvement under high mud content conditions are achieved. Provides high-efficiency low-temperature premature strength agent suitable for concrete crack repair.
Patent Information
- Application Number
- CN202411414725.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing early strength agent fails in low temperature environments, making it difficult to significantly improve the early strength of concrete under high mud content conditions, resulting in limited application of restoration materials.
Using the POSS structure of a stool as the main chain, the low-temperature early strength agent of the stool-type structure is synthesized through open-loop polymerization, catalysis, substitution-catalysis-copolymerization and ATRP reactions, which increases the molecular size effect and can Adsorb groups to improve the effects of reducing water, viscosity and dispersion.
It significantly improves the early strength of concrete under high mud content and low temperature environments, improves the viscosity and dispersion properties of restoration materials, extends the construction cycle, and enhances the restoration effect.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of on-site treatment of building materials and repair of existing buildings, in particular to a method for repairing concrete cracks at low temperature and an application thereof and a concrete crack repairing agent. Background Art
[0002] With the acceleration of infrastructure construction and the advancement of residential industrialization, engineering projects are gradually developing in the direction of complexity and diversification. Driven by production quality and production efficiency, new requirements are put forward for concrete performance, especially in engineering reinforcement and maintenance. However, a large amount of concrete is affected by environmental erosion, external impact, concrete shrinkage deformation and constraint, overload and other effects during service. Cracks have become the most common manifestation of concrete diseases. The generation of cracks will accelerate the deterioration of concrete, aggravate the corrosion of steel bars, significantly shorten the service life of the project, and even endanger the safety of buildings and concrete structures. Crack grouting construction technology is one of the most effective methods to repair cracks. However, existing repair materials still have problems such as high viscosity, high brittleness, low early strength, large shrinkage deformation, low bonding strength, and long curing time. Therefore, it is urgent to develop a new repair agent with excellent repair effect and no deterioration of other properties.
[0003] As a key component in concrete, early strength agent can significantly promote cement hydration and achieve excellent accelerating and early strength effect. It is widely used in rapid repair, low-temperature construction and prefabricated components. Therefore, if early strength agent is introduced into the repair material, its repair effect can be significantly enhanced. At present, traditional early strength agent is mainly divided into inorganic salts, organic matter and inorganic salt-organic composite. Among them, inorganic salts are mainly chlorides, sulfates and nitrates, organic matter is mainly triethanolamine, triisopropanolamine, early strength water reducer, inorganic salt-organic composite is mainly carbonate-alcoholamine composite, chloride-alcoholamine composite, inorganic salt-early strength water reducer composite. However, the Cl- introduced in traditional early strength agent is easy to cause corrosion of reinforced concrete, and sulfate causes salt precipitation on the surface of concrete, and has poor adaptability to concrete. In addition, traditional early strength agent is mainly used for concrete under normal temperature environment, and cannot play a good early strength and repair effect in low temperature environment. The decline in the stability of the early strength agent's effectiveness directly affects the application performance of the repair material and then affects the engineering quality of concrete, which seriously restricts the promotion and use of repair materials. Therefore, it is necessary to innovate the molecular structure design and develop a low-temperature early strength agent suitable for low ambient temperature, high mud content, rapid repair and large-area repair.
[0004] Innovative design of molecular structure is an effective technical means to improve the application performance of early strength agent. The POSS structure contains a large number of Si-O bonds and a strong molecular size effect, and has a certain mud resistance and low-temperature strengthening effect. Designing a series of stool-type POSS structure as the main chain and grafting adsorbable monomers and dispersed monomers will help to achieve the synergistic effect of dispersion, mud resistance, low-temperature strengthening and viscosity reduction. Therefore, this scheme prepares the series of stool-type POSS structure main chain through ring-opening polymerization, and then obtains the incomplete condensation series of stool-type structure main chain through catalysis, and then obtains the polymer incomplete condensation series of stool-type structure through substitution-catalysis-copolymerization reaction, and then prepares the early strength agent through substitution-ATRP reaction. The formed polymer has a multi-POSS molecular structure, realizes a large molecular size effect, carboxyl, silanol, sulfonic acid and phosphate synergistic effect, has excellent mud resistance, strengthening, dispersion and viscosity reduction effects, and can innovate and break through the poor adaptability of traditional early strength agents, the early strength effect is not significant under low temperature conditions, and the problem of poor dispersion ability.
[0005] At present, most researchers focus on modifying traditional water reducing agents. It is difficult to significantly improve the early strength of concrete by simply introducing groups or modifying polyether side chains. Moreover, most patents only focus on the research on the effect of improving the early strength of concrete under normal temperature. However, many early strength agents lose their activity under high mud content and low temperature curing environment, making it difficult to achieve the effect of early strength agents on the early strength of concrete, which limits the promotion and application of repair materials containing early strength agents. Therefore, it is urgent to develop new molecular structure early strength agents. It is necessary to innovate based on the concept of molecular structure design to synthesize water reducing agents containing POSS structure, carboxyl, sulfonic acid and phosphoric acid groups at the same time. The molecular structure of early strength agents can be precisely controlled by the synthesis methods of ring-opening polymerization, catalysis, substitution-catalysis-copolymerization and substitution-ATRP, so that the synthesized early strength agents can not only play the role of water reduction and viscosity reduction, but also ensure the early strength development of concrete. The synthesis method is easy to control, which is conducive to the promotion of industrialization. There are no relevant reports on this work at home and abroad, especially in the field of on-site processing of building materials and repair technology of existing buildings. There are no relevant reports on concrete crack repair. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a method for repairing concrete cracks at low temperature, which is reliable in implementation, flexible in application and has good repair effect on concrete cracks at low temperature, and its application and concrete crack repair agent.
[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0008] A method for repairing concrete cracks at low temperature, comprising:
[0009] S01. Pre-treat concrete cracks to remove dust, oil stains and loose aggregates on the surface and inside of the cracks. At the same time, wet the surface and inside of the cracks to improve the adhesion and bonding between the repair agent and the concrete;
[0010] S02, mixing water and concrete repair agent in a mass ratio of 0.1-0.3:1 to obtain a repair material. In this step, the concrete repair agent and water can be poured into a mixer and stirred to obtain a repair material.
[0011] S03. Inject the repair material into the interior and surface of the concrete crack, and then spread it evenly to allow the repair material to fill the interior of the crack and coat the surface of the crack. The repair material is applied to the crack surface in two layers. The thickness of the first layer of repair material is 0.6-0.8 mm, and the thickness of the second layer of repair material is 0.4-0.7 mm.
[0012] As a possible implementation mode, further, in the present solution S02, the components of the concrete repair agent include, by weight: 30-40 parts of Portland cement; 40-50 parts of sulphoaluminate cement; 7-29 parts of sand; and 1-3 parts of low-temperature early strength agent.
[0013] As a preferred implementation option, preferably, the preparation method of the concrete repair agent described in this scheme includes:
[0014] Portland cement, sulphoaluminate cement and sand are measured by weighing scales and transported to a mixer for mixing for 9-15 minutes;
[0015] The low-temperature early strength agent is added into the mixer and stirred for 20-30 minutes to obtain a bench-type structural component low-temperature concrete crack repair agent.
[0016] As a preferred implementation option, preferably, the grade of the silicate cement in this scheme is P·O 42.5, P·O 52.5, P·I 42.5 or P·I 52.5; the strength grade of the sulphoaluminate cement is 42.5 or 52.5; and the sand is standard sand.
[0017] As a preferred implementation option, preferably, the low-temperature early strength agent described in this scheme is a low-temperature early strength agent with a string-stool structure component, and its molecular structure is as follows:
[0018]
[0019] Wherein, a, b, c, p, q, r, w, x, y, z, n are integers representing the number of repeating units of each part in the polymer, a is in the range of 3-10, b is in the range of 5-20, c is in the range of 5-20, w is in the range of 4-13, x is in the range of 4-13, y is in the range of 5-17, z is in the range of 2-7, p is in the range of 3-10, q is in the range of 5-20, r is in the range of 5-20, and n is in the range of 10-150;
[0020] R1 is CH2, CH2CH2 or CH2CH2CH2, R2 is CH2CH2CH2, CH2CH2COOCH2CH2, CH2CH2COOCH2CH2OCH2CH2, CH2CH2COOCH2CH2OCH2CH2, CH2CH2COOCH2CH2OCH2CH2OCH2CH2 or CH2CH2COOCH2CH2OCH2CH2OCH2CH2OCH2CH2, R3 is H or CH3, R4 is Na or K, R5 is H or Na, and R6 is CH2, CH2CH2 or O(CH2CH2O)2.
[0021] As a preferred implementation option, preferably, the low-temperature early strength agent of the tandem bench structure component described in this scheme is prepared by ring-opening polymerization of hydroxy POSS and epoxy halogenated alkane to prepare the tandem bench structure main chain, and then functionally modified by catalysis, substitution-catalysis-copolymerization reaction in sequence to obtain a polymer incomplete condensation tandem bench structure, and then subjected to substitution-ATRP reaction with halogenated compounds, unsaturated carboxylate small monomers, unsaturated sulfonic acid small monomers and polyether macromonomers to obtain it.
[0022] As a preferred implementation option, preferably, the preparation method of the string stool structure component low temperature early strength agent described in this scheme includes:
[0023] (1) Preparation of the tandem stool structure main chain: hydroxy POSS and an organic solvent are mixed evenly and added to a reactor, and stirred and dissolved at 20-30 °C for 2-6 hours, and then 10-50% by mass of an alkaline solvent is added to adjust the pH value of the mixed solution to 10-14, and then epoxy halides are added thereto, and the temperature is raised to 40-80 °C for ring-opening polymerization. After reacting for 5-24 hours, the organic solvent and by-products are removed by reduced pressure distillation to obtain the tandem stool structure main chain;
[0024] (2) Preparation of an incompletely condensed tandem stool structure main chain: dissolve the tandem stool structure main chain obtained in step (1) in an organic solvent, add 10-50% by mass of an alkaline solvent, heat to 60-80°C, react for 2-6 hours, and remove the organic solvent and by-products by vacuum distillation to obtain an incompletely condensed tandem stool structure main chain;
[0025] (3) Preparation of polymer incomplete condensation tandem bench structure: the main chain of the incomplete condensation tandem bench structure obtained in step (2), halogenated silane, organic alkane and ethylamine organic matter are sequentially added into the reactor, and a substitution reaction is carried out at 0-10°C. After the reaction for 1-5 hours, an unsaturated ester small monomer, a karstedt catalyst and an organic solvent are added, and the temperature is raised to 30-60°C for catalytic reaction for 2-24 hours. Then, an unsaturated carboxylate small monomer and an unsaturated phosphoric acid small monomer are sequentially added, and a copolymerization reaction is carried out at 40-80°C. After the reaction for 3-8 hours, the organic solvent and by-products are removed by reduced pressure distillation to obtain a polymer incomplete condensation tandem bench structure;
[0026] (4) Preparation of low-temperature early strength agent of tandem stool structure component: The product of the incomplete condensation tandem stool structure of the polymer obtained in step (3) and the solvent are mixed evenly and added to the reactor, and then the halogenated compound is added to carry out substitution reaction at 0-40°C. After the reaction for 12-48 hours, transition metal halide, ligand, unsaturated carboxylic acid salt small monomer, unsaturated sulfonic acid small monomer and polyether macromonomer are added. Under nitrogen protection, the temperature is continuously raised to 50-100°C for ATRP reaction. The reaction is carried out for 5-60 hours, and the organic solvent and by-products are removed by desalination and reduced pressure distillation to obtain a low-temperature early strength agent of tandem stool structure component.
[0027] As a preferred implementation option, preferably, the organic solvent in step (1) of this scheme is tetrahydrofuran or dimethyl sulfoxide, and the mass ratio of the organic solvent to the hydroxy POSS is 2-10:1;
[0028] The alkaline solvent in step (1) is one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide or ammonium hydroxide, and the molar ratio of the alkaline solvent to the hydroxy POSS in step (1) is 0.1-2:1;
[0029] The epoxy haloalkane described in step (1) is epichlorohydrin, epibromohydrin, epiiodohydrin or 3-chloro-2-methyl-1,2-epoxypropane, and the molar ratio of the amount used to the hydroxy POSS described in step (1) is 0.1-2:1;
[0030] The organic solvent in step (2) is tetrahydrofuran or dimethyl sulfoxide, and the mass ratio of the organic solvent to the main chain of the tandem bench structure obtained in step (1) is 2-10:1;
[0031] The alkaline solvent in step (2) is one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide or ammonium hydroxide, and the molar ratio of the alkaline solvent to the main chain of the bench-like structure obtained in step (1) is 5-13:1;
[0032] The halosilane in step (3) is chlorodimethylsilane, bromopropyldimethylsilane or iodomethyldimethylsilane, and the molar ratio of the amount to the main chain of the incompletely condensed tandem bench structure obtained in step (2) is 4-13:1;
[0033] The organic alkane in step (3) is methane, ethane, propane, butane or hexane, and the mass ratio of the organic alkane used to the main chain of the incompletely condensed tandem bench structure obtained in step (2) is 10-30:1;
[0034] The ethylamine organic compound in step (3) is diethylamine or triethylamine, and the mass ratio of the amount used to the main chain of the incompletely condensed tandem bench structure obtained in step (2) is 0.04-0.6:1;
[0035] The unsaturated ester small monomer in step (3) is allyl methacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate or tetraethylene glycol dimethacrylate, and the molar ratio of the unsaturated ester small monomer to the incompletely condensed tandem bench structure main chain obtained in step (2) is 7-23:1;
[0036] The mass ratio of the amount of the Karstedt catalyst used in step (3) to the main chain of the incompletely condensed tandem bench structure obtained in step (2) is 0.01-0.1:1;
[0037] The organic solvent in step (3) is tetrahydrofuran or dimethyl sulfoxide in step (1), and the mass ratio of the organic solvent to the main chain of the incompletely condensed tandem bench structure obtained in step (2) is 2-10:1;
[0038] The unsaturated carboxylate small monomer in step (3) is sodium acrylate, sodium methacrylate, potassium acrylate or potassium methacrylate, and the molar ratio of the unsaturated carboxylate small monomer to the incompletely condensed tandem bench structure main chain obtained in step (2) is 9-33:1;
[0039] The unsaturated phosphoric acid monomer described in step (3) is 2-(methacryloyloxy)ethyl phosphate, vinylphosphonic acid or 2-methylvinylphosphonic acid, and the molar ratio of the unsaturated phosphoric acid monomer to the incompletely condensed tandem bench structure main chain obtained in step (2) is 9-33:1;
[0040] The solvent in step (4) is dichloromethane, dichloropropane, trichloromethane or trichloroethane, and the mass ratio of the solvent to the incompletely condensed polymer tandem bench structure obtained in step (3) is 5-20:1;
[0041] The halogenated compound in step (4) is 2-bromoisobutyryl bromide or 2-chloroisobutyryl chloride, and the molar ratio of the amount used to the incompletely condensed tandem bench structure of the polymer obtained in step (3) is 0.5-17:1;
[0042] The transition metal halide in step (4) is cuprous bromide, ferrous bromide, cuprous chloride, ferrous bromide or ferrous chloride, and the molar ratio of the amount to the incompletely condensed tandem bench structure of the polymer obtained in step (3) is 5-17:1;
[0043] The ligand in step (4) is N,N,N,N,N-pentamethyldiethylenetriamine, 2,2-bipyridine, 1,1,4,7,10,10-hexamethyltriethylenetetramine, N,N,N,N-tetra[(2-pyridyl)methyl]ethylenediamine or tri[2-(dimethylamino)ethyl]amine, and the molar ratio of the amount used to the incompletely condensed tandem bench structure of the polymer obtained in step (3) is 4-18:1;
[0044] The unsaturated carboxylic acid monomer in step (4) is the unsaturated carboxylate small monomer in step (3), which is sodium acrylate, sodium methacrylate, potassium acrylate or potassium methacrylate, and the molar ratio of the amount used to the incomplete condensation tandem bench structure of the polymer obtained in step (3) is 8-27:1;
[0045] The unsaturated sulfonic acid small monomer described in step (4) is 2-acrylamide-2-methylpropanesulfonic acid or 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonic acid sodium salt, and the molar ratio of the amount used to the incompletely condensed tandem bench structure of the polymer obtained in step (3) is 10-37:1;
[0046] The polyether macromonomer described in step (4) is methyl allyl polyoxyethylene ether, isopentanol polyethoxyethylene ether or butanediol monovinyl polyoxyethylene ether with a molecular weight of 2000-5000 g / mol, and the molar ratio of the amount used to the incomplete condensation tandem bench structure of the polymer obtained in step (3) is 10-37:1;
[0047] The salt removed in step (4) is one or more of cuprous bromide, cupric chloride, cupric bromide, ferric bromide, cuprous chloride, ferric chloride, ferrous bromide or ferrous chloride.
[0048] Based on the above, the present invention also provides a method for repairing concrete cracks in roads, bridges and building structures, which uses the above-mentioned method for repairing concrete cracks at low temperature.
[0049] Based on the above, the present scheme also provides a concrete crack repair agent, which includes a tandem bench structure component low-temperature early strength agent, wherein the tandem bench structure component low-temperature early strength agent is prepared by ring-opening polymerization of hydroxy POSS and epoxy halide to form a tandem bench structure main chain, and then functionally modified by catalysis, substitution-catalysis-copolymerization reaction in sequence to obtain a polymer incomplete condensation tandem bench structure, and then subjected to substitution-ATRP reaction with halogenated compounds, unsaturated carboxylate small monomers, unsaturated sulfonic acid small monomers and polyether macromonomers to obtain the structure.
[0050] By adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0051] 1. The method for low-temperature repair of concrete cracks in this scheme uses a low-temperature early strength agent with a bench-like structure component. Based on an innovative molecular structure design, a single hydroxyl POSS structure is polymerized by ring-opening polymerization to form a bench-like structure with multiple POSS structures as the main chain, and then catalyzed, substituted, and copolymerized with strong bases, halogenated silanes, unsaturated ester small monomers, unsaturated carboxylate small monomers, and unsaturated phosphoric acid small monomers to obtain an incomplete condensation bench-like structure of a polymer containing multiple adsorption groups, thereby increasing the adsorption capacity of the polymer, and then functionalized by substitution + ATRP reaction to obtain a "bench-like" structure early strength agent containing long side chains. The molecular structure of this early strength agent contains a large-size effect chain-type POSS main chain, a large number of carboxyl, silanol, sulfonic acid and phosphate adsorbable groups, and a large number of long side chains. The synergistic effect between them enables the early strength agent to exhibit excellent water-reducing and viscosity-reducing effects and significantly improve the early strength of concrete under high mud content and low temperature environments. Compared with similar products on the market, the effect is better. It is an innovation and breakthrough in the molecular structure design and preparation of early strength agents, and provides technical guidance for the in-depth research and promotion of early strength agents in the future.
[0052] 2. The low-temperature early strength agent with a bench-like structure component used in the method for low-temperature repair of concrete cracks in this scheme is different from the current mainstream direction of preparing early strength agents by modifying the POSS structure. This scheme breaks through the preparation mode of early strength agents with a "single" POSS structure, and innovatively introduces an independently synthesized "stool-like" POSS structure main chain with a unique molecular structure, and designs to introduce a large number of adsorbable groups and long side chains through catalysis, substitution, and polymerization, thereby increasing the size effect of the polymer and the types and contents of functional groups on the molecular chain, and improving the overall effectiveness and interaction force in space, making the molecular chain stretch less likely to deform, avoiding absorption and consumption by clay, and macroscopically improving the dispersion performance and early strength of concrete, with significant performance advantages and application prospects.
[0053] 3. The low-temperature early strength agent of the string stool type structure component used in the method of low-temperature repair of concrete cracks in this scheme is compared with the traditional early strength agent. The "string stool type" structure early strength agent designed and synthesized in this scheme has excellent anti-mud effect, early strength effect and dispersion effect. First, the spatial size of the main chain of the "stool-like" POSS structure is much larger than the distance between clay layers, which prevents the intercalation adsorption of the long side chains of the water reducer on the clay; secondly, the main chain of the "stool-like" POSS structure contains a large number of Si-O skeletons similar to those in the cement structure, which makes it have a strong interaction force with cement and can act preferentially on the surface of cement particles, inhibiting its adsorption on the clay surface; in addition, the Si-O skeleton contained in the main chain of the "stool-like" POSS structure has a significant nucleation effect on the calcium silicate formed by cement hydration, reduces the interfacial energy between the polymer and the hydration product, improves the density of the concrete, and has an excellent early strength effect, especially in low temperature environments; finally, a large number of adsorbable groups and long side chains are innovatively introduced on the main chain of the structure, which increases the repulsive force between cement particles, so that the prepared early strength agent has excellent water-reducing and dispersion effects, which can significantly reduce the viscosity of the repair material.
[0054] 4. Compared with traditional early strength agents, the synthesis method of the low-temperature early strength agent of the string bench structure component used in the method of low-temperature repair of concrete cracks in this scheme is more controllable by the ATRP method, the source of reaction raw materials is widely available, the price is low, safe and environmentally friendly, the production process is simple to operate, the energy consumption is low, there are no special requirements for equipment and experimental environment, and it is easy to realize industrial production.
[0055] 5. The "string bench type" structural early strength agent independently synthesized in this scheme is formulated as a concrete crack repair agent, which has good early strength ability, viscosity reduction ability, repair ability, mud resistance and low temperature adaptability. The repaired concrete can achieve an appearance and performance matching the original concrete. The formula is simple, easy to mix, and the repair time period is short, which reduces the construction period. It solves the problem of normal construction and slow early strength development in high mud content systems, low temperature environments and even negative temperature environments, and has a large application market and potential. DETAILED DESCRIPTION
[0056] The present invention will be further described in detail below in conjunction with the embodiments. It is particularly noted that the following embodiments are only used to illustrate the present invention, but are not intended to limit the scope of the present invention. Similarly, the following embodiments are only partial embodiments of the present invention rather than all embodiments, and all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention.
[0057] This embodiment provides a method for repairing concrete cracks at low temperature, which includes:
[0058] S01. Pre-treat concrete cracks to remove dust, oil stains and loose aggregates on the surface and inside of the cracks. At the same time, wet the surface and inside of the cracks to improve the adhesion and bonding between the repair agent and the concrete;
[0059] S02, mixing water and concrete repair agent in a mass ratio of 0.1-0.3:1 to obtain a repair material. In this step, the concrete repair agent and water can be poured into a mixer and stirred to obtain a repair material.
[0060] S03. Inject the repair material into the interior and surface of the concrete crack, and then spread it evenly to allow the repair material to fill the interior of the crack and coat the surface of the crack. The repair material is applied to the crack surface in two layers. The thickness of the first layer of repair material is 0.6-0.8 mm, and the thickness of the second layer of repair material is 0.4-0.7 mm.
[0061] In the present scheme S02, the components of the concrete repair agent include, by weight: 30-40 parts of Portland cement; 40-50 parts of sulphoaluminate cement; 7-29 parts of sand; and 1-3 parts of low-temperature early strength agent.
[0062] The preparation method of the concrete repair agent described in this scheme includes:
[0063] Portland cement, sulphoaluminate cement and sand are measured by weighing scales and transported to a mixer for mixing for 9-15 minutes;
[0064] The low-temperature early strength agent is added into the mixer and stirred for 20-30 minutes to obtain a bench-type structural component low-temperature concrete crack repair agent.
[0065] Preferably, the grade of the silicate cement in this solution is P·O 42.5, P·O 52.5, P·I 42.5 or P·I 52.5; the strength grade of the sulphoaluminate cement is 42.5 or 52.5; and the sand is standard sand.
[0066] The preparation method of the low-temperature early strength agent of the string-stool structure component described in this scheme comprises:
[0067] (1) Preparation of the tandem stool structure main chain: hydroxy POSS and an organic solvent are mixed evenly and added to a reactor, and stirred and dissolved at 20-30 °C for 2-6 hours, and then 10-50% by mass of an alkaline solvent is added to adjust the pH value of the mixed solution to 10-14, and then epoxy halides are added thereto, and the temperature is raised to 40-80 °C for ring-opening polymerization. After reacting for 5-24 hours, the organic solvent and by-products are removed by reduced pressure distillation to obtain the tandem stool structure main chain;
[0068] (2) Preparation of an incompletely condensed tandem stool structure main chain: dissolve the tandem stool structure main chain obtained in step (1) in an organic solvent, add 10-50% by mass of an alkaline solvent, heat to 60-80°C, react for 2-6 hours, and remove the organic solvent and by-products by vacuum distillation to obtain an incompletely condensed tandem stool structure main chain;
[0069] (3) Preparation of polymer incomplete condensation tandem bench structure: the main chain of the incomplete condensation tandem bench structure obtained in step (2), halogenated silane, organic alkane and ethylamine organic matter are sequentially added into the reactor, and a substitution reaction is carried out at 0-10°C. After the reaction for 1-5 hours, an unsaturated ester small monomer, a karstedt catalyst and an organic solvent are added, and the temperature is raised to 30-60°C for catalytic reaction for 2-24 hours. Then, an unsaturated carboxylate small monomer and an unsaturated phosphoric acid small monomer are sequentially added, and a copolymerization reaction is carried out at 40-80°C. After the reaction for 3-8 hours, the organic solvent and by-products are removed by reduced pressure distillation to obtain a polymer incomplete condensation tandem bench structure;
[0070] (4) Preparation of low-temperature early strength agent of tandem stool structure component: The product of the incomplete condensation tandem stool structure of the polymer obtained in step (3) and the solvent are mixed evenly and added to the reactor, and then the halogenated compound is added to carry out substitution reaction at 0-40°C. After the reaction for 12-48 hours, transition metal halide, ligand, unsaturated carboxylic acid salt small monomer, unsaturated sulfonic acid small monomer and polyether macromonomer are added. Under nitrogen protection, the temperature is continuously raised to 50-100°C for ATRP reaction. The reaction is carried out for 5-60 hours, and the organic solvent and by-products are removed by desalination and reduced pressure distillation to obtain a low-temperature early strength agent of tandem stool structure component.
[0071] As a preferred implementation option, preferably, the organic solvent described in step (1) of this scheme is tetrahydrofuran or dimethyl sulfoxide, and the mass ratio of the amount to the hydroxy POSS is 2-10:1; the alkaline solvent described in step (1) is one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide or ammonium hydroxide, and the molar ratio of the amount to the hydroxy POSS described in step (1) is 0.1-2:1; the epoxy halide described in step (1) is epichlorohydrin, epibromohydrin, epiiodohydrin or 3-chloro-2-methyl-1,2-epoxypropane, and the molar ratio of the amount to the hydroxy POSS described in step (1) is 0.1-2:1;
[0072] The organic solvent in step (2) is tetrahydrofuran or dimethyl sulfoxide, and the mass ratio of the organic solvent used to the main chain of the tandem bench structure obtained in step (1) is 2-10:1; the alkaline solvent in step (2) is one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide or ammonium hydroxide, and the molar ratio of the organic solvent used to the main chain of the tandem bench structure obtained in step (1) is 5-13:1;
[0073] The halogenated silane described in step (3) is chlorodimethylsilane, bromopropyldimethylsilane or iodomethyldimethylsilane, and the molar ratio of the amount used to the main chain of the incomplete condensation cascade stool structure obtained in step (2) is 4-13:1; the organic alkane described in step (3) is methane, ethane, propane, butane or hexane, and the mass ratio of the amount used to the main chain of the incomplete condensation cascade stool structure obtained in step (2) is 10-30:1; the ethylamine organic matter described in step (3) is diethylamine or triethylamine, and the mass ratio of the amount used to the main chain of the incomplete condensation cascade stool structure obtained in step (2) is 0.04-0.6:1; the unsaturated ester small monomer described in step (3) is allyl methacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate or tetraethylene glycol dimethacrylate, and the molar ratio of the amount used to the main chain of the incomplete condensation cascade stool structure obtained in step (2) is The mass ratio of the amount of the karstedt catalyst in step (3) to the main chain of the incomplete condensation cascade stool structure obtained in step (2) is 0.01-0.1:1; the organic solvent in step (3) is tetrahydrofuran or dimethyl sulfoxide in step (1), and the mass ratio of the amount to the main chain of the incomplete condensation cascade stool structure obtained in step (2) is 2-10:1; the unsaturated carboxylate small monomer in step (3) is sodium acrylate, sodium methacrylate, potassium acrylate or potassium methacrylate, and the molar ratio of the amount to the main chain of the incomplete condensation cascade stool structure obtained in step (2) is 9-33:1; the unsaturated phosphoric acid small monomer in step (3) is 2-(methacryloyloxy)ethyl phosphate, vinylphosphonic acid or 2-methylvinylphosphonic acid, and the molar ratio of the amount to the main chain of the incomplete condensation cascade stool structure obtained in step (2) is 9-33:1;
[0074] The solvent in step (4) is dichloromethane, dichloropropane, chloroform or trichloroethane, and the mass ratio of the amount used to the incomplete condensation cascade structure of the polymer obtained in step (3) is 5-20:1; the halogenated compound in step (4) is 2-bromoisobutyryl bromide or 2-chloroisobutyryl chloride, and the molar ratio of the amount used to the incomplete condensation cascade structure of the polymer obtained in step (3) is 0.5-17:1; the transition metal halide in step (4) is cuprous bromide, ferrous bromide, cuprous chloride, ferrous bromide or ferrous chloride, and the molar ratio of the amount used to the incomplete condensation cascade structure of the polymer obtained in step (3) is 5-17:1;
[0075] The ligand in step (4) is N,N,N,N,N-pentamethyldiethylenetriamine, 2,2-bipyridine, 1,1,4,7,10,10-hexamethyltriethylenetetramine, N,N,N,N-tetra[(2-pyridyl)methyl]ethylenediamine or tri[2-(dimethylamino)ethyl]amine, and the molar ratio of the amount used to the incompletely condensed tandem bench structure of the polymer obtained in step (3) is 4-18:1; the unsaturated carboxylic acid monomer in step (4) is the unsaturated carboxylic acid monomer in step (3) The salt small monomer is sodium acrylate, sodium methacrylate, potassium acrylate or potassium methacrylate, and the molar ratio of the amount used to the incomplete condensation cascade bench structure of the polymer obtained in step (3) is 8-27:1; the unsaturated sulfonic acid small monomer described in step (4) is 2-acrylamide-2-methylpropanesulfonic acid or 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonic acid sodium salt, and the molar ratio of the amount used to the incomplete condensation cascade bench structure of the polymer obtained in step (3) is 10-37:1;
[0076] The polyether macromonomer described in step (4) is methyl allyl polyoxyethylene ether, isopentanol polyethoxyethylene ether or butanediol monovinyl polyoxyethylene ether with a molecular weight of 2000-5000 g / mol, and the molar ratio of the amount used to the incomplete condensation tandem bench structure of the polymer obtained in step (3) is 10-37:1; the salt removed in step (4) is one or more of cuprous bromide, cupric chloride, cupric bromide, ferric bromide, cuprous chloride, ferric chloride, ferrous bromide or ferrous chloride.
[0077] The low-temperature early strength agent described in this scheme is a low-temperature early strength agent with a string-stool structure component, and its molecular structure is as follows:
[0078]
[0079] Wherein, a, b, c, p, q, r, w, x, y, z, n are integers representing the number of repeating units of each part in the polymer, a is in the range of 3-10, b is in the range of 5-20, c is in the range of 5-20, w is in the range of 4-13, x is in the range of 4-13, y is in the range of 5-17, z is in the range of 2-7, p is in the range of 3-10, q is in the range of 5-20, r is in the range of 5-20, and n is in the range of 10-150;
[0080] R1 is CH2, CH2CH2 or CH2CH2CH2, R2 is CH2CH2CH2, CH2CH2COOCH2CH2, CH2CH2COOCH2CH2OCH2CH2, CH2CH2COOCH2CH2OCH2CH2, CH2CH2COOCH2CH2OCH2CH2OCH2CH2 or CH2CH2COOCH2CH2OCH2CH2OCH2CH2OCH2CH2, R3 is H or CH3, R4 is Na or K, R5 is H or Na, and R6 is CH2, CH2CH2 or O(CH2CH2O)2.
[0081] Based on the above, the present invention also provides a method for repairing concrete cracks in roads, bridges and building structures, which uses the above-mentioned method for repairing concrete cracks at low temperature.
[0082] In order to facilitate the detailed description of the low-temperature early strength agent, a component of the bench-like structure of the concrete repair agent of the present invention, a comparison is made in combination with a plurality of embodiments and comparative examples as follows.
[0083] The grade of silicate cement used in each embodiment is P·O 52.5; the strength grade of sulphoaluminate cement is 42.5; and the sand is standard sand.
[0084] Example 1
[0085] This embodiment provides a formula of a concrete repair agent, and its components, measured by weight, include: 30 parts of Portland cement; 40 parts of sulphoaluminate cement; 29 parts of sand; and 1 part of a low-temperature early strength agent.
[0086] Among them, the low-temperature early strength agent in the component is a low-temperature early strength agent of a string-stool structure component, and its preparation method includes:
[0087] (1) Preparation of the tandem stool structure main chain: First, 25 g of hydroxy POSS and 50 g of tetrahydrofuran were added to the reactor and stirred for dissolution at 20 °C for 2 hours. Then, 0.06 g of 10% sodium hydroxide solution was added to adjust the pH value of the mixture to 10. 0.20 g of epibromopropane was added to the mixture and reacted at 40 °C for 5 hours. The organic solvent and by-products were removed by reduced pressure distillation to obtain the tandem stool structure main chain.
[0088] (2) Preparation of incomplete condensation tandem stool structure main chain: 50 g tandem stool structure main chain and 100 g tetrahydrofuran were added to the reactor, followed by 0.39 g of 10% sodium hydroxide solution, stirred at 60 °C for 2 hours, and the organic solvent and by-products were removed by reduced pressure distillation to obtain the incomplete condensation tandem stool structure main chain;
[0089] (3) Preparation of polymer incomplete condensation tandem stool structure: 25 g of incomplete condensation tandem stool structure main chain, 0.71 g of bromopropyldimethylsilane, 250 g of methane, and 1 g of diethylamine were added to the reactor in sequence. After reacting at 0°C for 1 hour, 1.36 g of ethylene glycol dimethacrylate, 0.25 g of Karstedt catalyst, and 50 g of tetrahydrofuran were added. The reaction was carried out at 30°C for 2 hours. Then, 1.31 g of cinnamic acid and 0.95 g of vinylphosphonic acid were added in sequence. The reaction was carried out at 40°C for 3 hours. The organic solvent and by-products were removed by reduced pressure distillation to obtain a polymer incomplete condensation tandem stool structure.
[0090] (4) Preparation of low-temperature early strength agent of cascade-like structure component: 50 g of polymer incomplete condensation cascade-like structure and 250 g of chloroform were mixed evenly and added to the reactor, and then 0.13 g of 2-chloroisobutyryl chloride was added. The mixture was reacted at 0 °C for 12 h. Then 0.91 g of cuprous chloride, 1.69 g of 1,1,4,7,10,10-hexamethyltriethylenetetramine, 2.68 g of m-chlorocinnamic acid, 4.21 g of 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonic acid sodium salt and 36.76 g of butanediol monovinyl polyoxyethylene ether were added. The mixture was sealed under nitrogen protection and the temperature was continued to rise to 50 °C for ATRP reaction. The mixture was reacted for 5 h. The organic solvent and by-products were removed by desalination and reduced pressure distillation to obtain a low-temperature early strength agent of cascade-like structure component.
[0091] Example 2
[0092] This embodiment provides a formula of a concrete repair agent, and its components, measured by weight, include: 40 parts of Portland cement; 45 parts of sulphoaluminate cement; 13 parts of sand; and 2 parts of low-temperature early strength agent.
[0093] Among them, the low-temperature early strength agent in the component is a low-temperature early strength agent of a string-stool structure component, and its preparation method includes:
[0094] (1) Preparation of the tandem stool structure main chain: First, 25 g of hydroxy POSS and 250 g of dimethyl sulfoxide were added to the reactor and stirred and dissolved at 30 °C for 6 hours. Then, 1.65 g of 50% potassium hydroxide solution was added to adjust the pH value of the mixture to 14. 4.02 g of 3-chloro-2-methyl-1,2-epoxypropane was added to the mixture and reacted at 80 °C for 24 hours. The organic solvent and by-products were removed by reduced pressure distillation to obtain the tandem stool structure main chain.
[0095] (2) Preparation of incomplete condensation tandem stool structure main chain: 50 g tandem stool structure main chain and 500 g dimethyl sulfoxide were added to the reactor, followed by 0.42 g of 50% potassium hydroxide solution, stirred at 80 °C for 6 hours, and the organic solvent and by-products were removed by vacuum distillation to obtain the incomplete condensation tandem stool structure main chain;
[0096] (3) Preparation of polymer incomplete condensation tandem bench structure: 25 g of incomplete condensation tandem bench structure main chain, 0.76 g of iodomethyldimethylsilane, 750 g of butane, and 15 g of triethylamine were added to the reactor in sequence. After reacting at 10 °C for 5 hours, 1.93 g of triethylene glycol dimethacrylate, 2.5 g of Karstedt catalyst, and 250 g of dimethyl sulfoxide were added. The reaction was carried out at 60 °C for 24 hours. Then, 1.13 g of fumaric acid and 1.18 g of 2-methylvinylphosphonic acid were added in sequence. The reaction was carried out at 80 °C for 8 hours. The organic solvent and by-products were removed by reduced pressure distillation to obtain a polymer incomplete condensation tandem bench structure.
[0097] (4) Preparation of low-temperature early strength agent of cascade-stool structure component: 50 g of polymer incomplete condensation cascade-stool structure and 1000 g of dichloropropane were mixed evenly and added to the reactor, and then 2.13 g of 2-bromoisobutyryl bromide was added. The mixture was reacted at 40 °C for 48 h. Then 1.99 g of ferrous bromide, 4.16 g of N,N,N,N-tetrakis[(2-pyridyl)methyl]ethylenediamine, 2.68 g of m-bromocinnamic acid, 3.34 g of 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonic acid sodium salt and 100.83 g of methyl allyl polyoxyethylene ether were added. The mixture was sealed under nitrogen protection and the temperature was continued to rise to 100 °C for ATRP reaction. The reaction was continued for 60 h. The organic solvent and by-products were removed by desalination and reduced pressure distillation to obtain a low-temperature early strength agent of cascade-stool structure component.
[0098] Example 3
[0099] This embodiment provides a formula of a concrete repair agent, and its components, measured by weight, include: 35 parts of Portland cement; 50 parts of sulphoaluminate cement; 12 parts of sand; and 3 parts of low-temperature early strength agent.
[0100] Among them, the low-temperature early strength agent in the component is a low-temperature early strength agent of a string-stool structure component, and its preparation method includes:
[0101] (1) Preparation of the tandem stool structure main chain: First, 25 g of hydroxy POSS and 125 g of tetrahydrofuran were added to the reactor and stirred for dissolution at 25 °C for 4 hours. Then, 0.59 g of 30% sodium hydroxide solution was added to adjust the pH value of the mixture to 14. 1.36 g of epichlorohydrin was added to the mixture and reacted at 80 °C for 24 hours. The organic solvent and by-products were removed by reduced pressure distillation to obtain the tandem stool structure main chain.
[0102] (2) Preparation of incomplete condensation tandem stool structure main chain: 50 g tandem stool structure main chain and 250 g tetrahydrofuran were added to the reactor, followed by 0.19 g of 30% sodium hydroxide solution, stirred at 70 °C for 4 hours, and the organic solvent and by-products were removed by reduced pressure distillation to obtain the incomplete condensation tandem stool structure main chain;
[0103] (3) Preparation of polymer incomplete condensation tandem stool structure: 25 g of incomplete condensation tandem stool structure main chain, 0.22 g of chlorodimethylsilane, 375 g of hexane, and 5 g of triethylamine were added to the reactor in sequence. After reacting at 5 °C for 5 hours, 0.55 g of allyl methacrylate, 1.25 g of Karstedt catalyst, and 125 g of tetrahydrofuran were added. The reaction was carried out at 45 °C for 20 hours. Then, 0.42 g of acrylic acid and 1.34 g of 2-(methacryloyloxy)ethyl phosphate were added in sequence. The reaction was carried out at 60 °C for 8 hours. The organic solvent and by-products were removed by reduced pressure distillation to obtain a polymer incomplete condensation tandem stool structure.
[0104] (4) Preparation of low-temperature early strength agent of cascade-stool structure component: 50 g of polymer incomplete condensation cascade-stool structure and 500 g of dichloromethane were mixed evenly and added to the reactor, and then 1.25 g of 2-bromoisobutyryl bromide was added. The mixture was reacted at 25 °C for 48 h. Then 0.78 g of cuprous bromide, 0.94 g of N,N,N,N,N-pentamethyldivinyltriamine, 0.78 g of acrylic acid, 2.26 g of 2,2-acrylamide-2-methylpropanesulfonic acid and 32.7 g of isopentanol polyethoxylated ether were added. The mixture was sealed under nitrogen protection and the temperature was continued to rise to 65 °C for ATRP reaction. The mixture was reacted for 24 h. The organic solvent and by-products were removed by desalination and reduced pressure distillation to obtain a low-temperature early strength agent of cascade-stool structure component.
[0105] Comparative Example 1
[0106] A commercially available early strength agent prepared from a quaternary ammonium salt early strength functional monomer is used as comparative example 1. Based on 100 parts of the total amount of the early strength agent, the amount of the quaternary ammonium salt early strength functional monomer is 5 parts.
[0107] Comparative Example 2
[0108] A commercially available early strength agent having a phosphonic acid group early strength functional monomer is used as comparative example 2. Based on 100 parts of the total amount of the early strength agent, the amount of the phosphonic acid group early strength functional monomer is 4 parts.
[0109] Comparative Example 3
[0110] A commercially available nano-crystal core early strength agent is used as comparative example 3, and the brand of the nano-crystal core early strength agent is SBT-510.
[0111] Comparison test
[0112] 1. Fluidity of cement paste
[0113] In order to investigate the effect of the bench-like early strength agent synthesized in this scheme on the fluidity of the repair material, the fluidity of the repair material mixed with the bench-like early strength agent prepared in Examples 1-3 and the early strength polycarboxylate water-reducing agent in Comparative Examples 1-3 was tested according to GB / T 8077-2012 under the same amount of water added. In the test, water and concrete repair agent were mixed at a mass ratio of 0.17:1. The examples used are repair materials mixed with the bench-like early strength agent synthesized in Examples 1-3 of this scheme, and the comparative examples used are repair materials mixed with commercially available early strength polycarboxylate water-reducing agents. The test results of the fluidity of the repair materials are shown in Table 1.
[0114] Table 1 Test results of fluidity of repair materials
[0115]
[0116] It can be seen from Table 1 that the repair material with the "string stool type" structural component early strength agent synthesized in the embodiment of this scheme has excellent flow properties and fluidity retention, and the dispersion and retention performance are better than the comparative example with the commercially available early strength polycarboxylic acid water reducer, indicating that the "string stool type" structural component early strength agent has excellent dispersion ability and cement adaptability, can significantly reduce the viscosity of the repair material, and is beneficial to the repair of cracks.
[0117] 2. Compressive strength of repair materials at different curing temperatures
[0118] In order to investigate the effect of the "string stool" structural component early strength agent synthesized in this scheme on the early strength development of repair materials under different temperature environments, the specimens were molded according to GB / T 50081-2019. In the test, water and concrete repair agent were mixed in a mass ratio of 0.17:1. After molding, the surface was covered with an impermeable film immediately, and then placed at -10~-5 ℃, -5~0 ℃ and 0~5 ℃ for curing for 24 hours. After demolding, the compressive strength of the specimens was tested for 1 day. The remaining specimens continued to be cured at -10~-5 ℃, -5~0 ℃ and 0~5 ℃ to the specified age, and the compressive strength of the specimens was tested for 3 days and 28 days, respectively. The test results are shown in Table 2.
[0119] Table 2 Compressive strength test results of repair materials / MPa
[0120]
[0121] As can be seen from Table 2, the early strength early agent of the "string stool type" structural component synthesized by the method of this scheme significantly improves the early strength and late strength of the repair material under different temperature environments, indicating that the prepared "string stool type" structural component early strength agent can promote the development of the early strength of the repair material under low temperature and negative temperature curing environment.
[0122] 3. Repair effect of repair materials at different curing temperatures
[0123] In order to investigate the repair effect of the "stool-like" structural component early strength agent synthesized in this scheme on the repair material under different temperature environments, in this test, concrete with strength grade C60 was selected as the repaired specimen, and its mix ratio is shown in Table 3. Among them, the cement used is Chengde Jinyu P·O 42.5 cement, the sand is a II zone continuous graded natural medium sand with a fineness modulus of 2.8 and a mud content of less than 2.1%, the stone is a 5~20 mm continuous graded crushed stone, the dosage of polycarboxylate water reducer is 0.2% of the mass of the cementitious material, and the specimen is molded according to GB / T 50081-2019.
[0124] The steel sheet method was used to make concrete cracks. The crack length was uniformly set to 60 mm. Steel sheets with thicknesses of 0.2 mm and 0.8 mm were made according to the predetermined crack width. During pouring, the steel sheets were vertically inserted into the mold in advance to make through cracks, and the surface was immediately covered with a waterproof film. Then, they were placed at -10~-5 ℃, -5~0 ℃, and 0~5 ℃ for curing for 6 hours. After the concrete had a certain strength and would not deform, the steel sheet was slowly pulled out vertically, and demolded after continuing to cure for 18 hours. Then, it was placed at -10~-5 ℃, -5~0 ℃, and 0~5 ℃ for curing for 28 days, then taken out and placed with the cracked surface facing up. The mass ratio of water to concrete repair agent was 0.17:1 to prepare the repair material, and the concrete cracks were repaired. The test results are shown in Table 4.
[0125] Table 3 C60 concrete mix ratio / kg / m 3
[0126]
[0127] Table 4 Repair effect of repair materials
[0128]
[0129] It can be seen from Table 4 that the "string stool type" structural component early strength agent synthesized by this scheme method has excellent repair effect under different temperature environments and can completely repair cracks, indicating that the prepared "string stool type" structural component early strength agent can promote the crack repair of repair materials in low temperature and negative temperature environments, thereby promoting the service life of civil engineering.
[0130] The above descriptions are only some embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Any equivalent device or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for repairing concrete cracks at low temperature, characterized in that: It includes: S01. Pre-treat concrete cracks to remove dust, oil stains and loose aggregates on the surface and inside of the cracks; S02, mixing water and concrete repair agent in a mass ratio of 0.1-0.3:1 and stirring evenly to obtain a repair material; S03, injecting the repair material into the interior and surface of the concrete crack, and then evenly applying it to fill the crack and coat the crack surface with the repair material, wherein the crack surface is constructed with two layers of repair material, the thickness of the first layer of repair material is 0.6-0.8 mm, and the thickness of the second layer of repair material is 0.4-0.7 mm; Among them, in S02, the components of the concrete repair agent include, by weight: 30-40 parts of silicate cement; 40-50 parts of sulphoaluminate cement; 7-29 parts of sand; 1-3 parts of low-temperature early strength agent; The low-temperature early strength agent is prepared by ring-opening polymerization of hydroxy POSS and epoxy halide to prepare a tandem stool structure main chain, and then functionally modified by catalysis, substitution-catalysis-copolymerization reaction to obtain a polymer incomplete condensation tandem stool structure, and then subjected to substitution-ATRP reaction with halogenated compounds, unsaturated carboxylate small monomers, unsaturated sulfonic acid small monomers and polyether macromonomers; The halogenated compound is 2-bromoisobutyryl bromide or 2-chloroisobutyryl chloride.
2. The method for repairing concrete cracks at low temperature as claimed in claim 1, characterized in that: The preparation method of the concrete repairing agent comprises: Portland cement, sulphoaluminate cement and sand are measured by weighing scales and transported to a mixer for mixing for 9-15 minutes; The low-temperature early strength agent is added into the mixer and stirred for 20-30 minutes to obtain a bench-type structural component low-temperature concrete crack repair agent.
3. The method for repairing concrete cracks at low temperature according to claim 1 or 2, characterized in that: The grade of the silicate cement is P·O 42.5, P·O 52.5, P·I 42.5 or P·I 52.5; the strength grade of the sulphoaluminate cement is 42.5 or 52.5; and the sand is standard sand.
4. The method for repairing concrete cracks at low temperature according to claim 1 or 2, characterized in that: The low-temperature early strength agent is a low-temperature early strength agent with a string-stool structure component, and its molecular structure is as follows: Wherein, a, b, c, p, q, r, w, x, y, z, n are integers representing the number of repeating units of each part in the polymer, a is in the range of 3-10, b is in the range of 5-20, c is in the range of 5-20, w is in the range of 4-13, x is in the range of 4-13, y is in the range of 5-17, z is in the range of 2-7, p is in the range of 3-10, q is in the range of 5-20, r is in the range of 5-20, and n is in the range of 10-150; R1 is CH2, CH2CH2 or CH2CH2CH2, R2 is CH2CH2CH2, CH2CH2COOCH2CH2, CH2CH2COOCH2CH2OCH2CH2, CH2CH2COOCH2CH2OCH2CH2, CH2CH2COOCH2CH2OCH2CH2OCH2CH2 or CH2CH2COOCH2CH2OCH2CH2OCH2CH2OCH2CH2, R3 is H or CH3, R4 is Na or K, R5 is H or Na, and R6 is CH2, CH2CH2 or O(CH2CH2O)2.
5. The method for repairing concrete cracks at low temperature as claimed in claim 4, characterized in that: The preparation method of the string stool type structural component low temperature early strength agent comprises: (1) Preparation of the tandem stool structure main chain: hydroxy POSS and an organic solvent are mixed evenly and added to a reactor, and stirred and dissolved at 20-30°C for 2-6 hours. Then, an alkaline solvent with a mass fraction of 10-50% is added to adjust the pH value of the mixed solution to 10-14, and then an epoxy halide is added thereto. The temperature is raised to 40-80°C for ring-opening polymerization. After reacting for 5-24 hours, the organic solvent and by-products are removed by reduced pressure distillation to obtain a tandem stool structure main chain; (2) Preparation of an incompletely condensed tandem stool structure main chain: dissolve the tandem stool structure main chain obtained in step (1) in an organic solvent, add 10-50% by mass of an alkaline solvent, heat to 60-80°C, react for 2-6 hours, and remove the organic solvent and by-products by vacuum distillation to obtain an incompletely condensed tandem stool structure main chain; (3) Preparation of a polymeric incomplete condensation tandem bench structure: the incomplete condensation tandem bench structure main chain of the product obtained in step (2), halogenated silane, organic alkane and ethylamine organic matter are sequentially added into a reactor, and a substitution reaction is carried out at 0-10°C. After the reaction for 1-5 hours, an unsaturated ester small monomer, a karstedt catalyst and an organic solvent are added, and the temperature is raised to 30-60°C for catalytic reaction for 2-24 hours. Then, an unsaturated carboxylate small monomer and an unsaturated phosphoric acid small monomer are sequentially added, and a copolymerization reaction is carried out at 40-80°C. After the reaction for 3-8 hours, the organic solvent and by-products are removed by reduced pressure distillation to obtain a polymeric incomplete condensation tandem bench structure; (4) Preparation of low-temperature early strength agent of tandem stool structure component: The product of the incomplete condensation tandem stool structure of the polymer obtained in step (3) and the solvent are mixed evenly and added to the reactor, and then the halogenated compound is added to carry out substitution reaction at 0-40°C. After the reaction for 12-48 hours, transition metal halide, ligand, unsaturated carboxylic acid salt small monomer, unsaturated sulfonic acid small monomer and polyether macromonomer are added. Under nitrogen protection, the temperature is continuously raised to 50-100°C for ATRP reaction. The reaction is carried out for 5-60 hours, and the organic solvent and by-products are removed by desalination and reduced pressure distillation to obtain a low-temperature early strength agent of tandem stool structure component.
6. The method for repairing concrete cracks at low temperature as claimed in claim 5, characterized in that: The organic solvent in step (1) is tetrahydrofuran or dimethyl sulfoxide, and the mass ratio of the organic solvent to the hydroxy POSS is 2-10:1; The alkaline solvent in step (1) is one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide or ammonium hydroxide, and the molar ratio of the alkaline solvent to the hydroxy POSS in step (1) is 0.1-2:1; The epoxy haloalkane described in step (1) is epichlorohydrin, epibromohydrin, epiiodohydrin or 3-chloro-2-methyl-1,2-epoxypropane, and the molar ratio of the amount used to the hydroxy POSS described in step (1) is 0.1-2:1; The organic solvent in step (2) is tetrahydrofuran or dimethyl sulfoxide, and the mass ratio of the organic solvent to the main chain of the tandem bench structure obtained in step (1) is 2-10:1; The alkaline solvent in step (2) is one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide or ammonium hydroxide, and the molar ratio of the alkaline solvent to the main chain of the bench-like structure obtained in step (1) is 5-13:1; The halosilane in step (3) is chlorodimethylsilane, bromopropyldimethylsilane or iodomethyldimethylsilane, and the molar ratio of the amount to the main chain of the incompletely condensed tandem bench structure obtained in step (2) is 4-13:1; The organic alkane in step (3) is methane, ethane, propane, butane or hexane, and the mass ratio of the organic alkane used to the main chain of the incompletely condensed tandem bench structure obtained in step (2) is 10-30:1; The ethylamine organic compound in step (3) is diethylamine or triethylamine, and the mass ratio of the amount used to the main chain of the incompletely condensed tandem bench structure obtained in step (2) is 0.04-0.6:1; The unsaturated ester small monomer in step (3) is allyl methacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate or tetraethylene glycol dimethacrylate, and the molar ratio of the unsaturated ester small monomer to the incompletely condensed tandem bench structure main chain obtained in step (2) is 7-23:1; The mass ratio of the amount of the Karstedt catalyst used in step (3) to the main chain of the incompletely condensed tandem bench structure obtained in step (2) is 0.01-0.1:1; The organic solvent in step (3) is tetrahydrofuran or dimethyl sulfoxide in step (1), and the mass ratio of the organic solvent to the main chain of the incompletely condensed tandem bench structure obtained in step (2) is 2-10:1; The unsaturated carboxylate small monomer in step (3) is sodium acrylate, sodium methacrylate, potassium acrylate or potassium methacrylate, and the molar ratio of the unsaturated carboxylate small monomer to the incompletely condensed tandem bench structure main chain obtained in step (2) is 9-33:1; The unsaturated phosphoric acid monomer described in step (3) is 2-(methacryloyloxy)ethyl phosphate, vinylphosphonic acid or 2-methylvinylphosphonic acid, and the molar ratio of the unsaturated phosphoric acid monomer to the incompletely condensed tandem bench structure main chain obtained in step (2) is 9-33:1; The solvent in step (4) is dichloromethane, dichloropropane, trichloromethane or trichloroethane, and the mass ratio of the solvent to the incompletely condensed polymer tandem bench structure obtained in step (3) is 5-20:1; The molar ratio of the amount of the halogenated compound used in step (4) to the incompletely condensed tandem bench structure of the polymer obtained in step (3) is 0.5-17:1; The transition metal halide in step (4) is cuprous bromide, ferrous bromide, cuprous chloride, ferrous bromide or ferrous chloride, and the molar ratio of the amount to the incompletely condensed tandem bench structure of the polymer obtained in step (3) is 5-17:1; The ligand in step (4) is N,N,N,N,N-pentamethyldiethylenetriamine, 2,2-bipyridine, 1,1,4,7,10,10-hexamethyltriethylenetetramine, N,N,N,N-tetra[(2-pyridyl)methyl]ethylenediamine or tri[2-(dimethylamino)ethyl]amine, and the molar ratio of the amount used to the incompletely condensed tandem bench structure of the polymer obtained in step (3) is 4-18:1; The unsaturated carboxylic acid monomer in step (4) is the unsaturated carboxylate small monomer in step (3), which is sodium acrylate, sodium methacrylate, potassium acrylate or potassium methacrylate, and the molar ratio of the amount used to the incomplete condensation tandem bench structure of the polymer obtained in step (3) is 8-27:1; The unsaturated sulfonic acid small monomer described in step (4) is 2-acrylamide-2-methylpropanesulfonic acid or 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonic acid sodium salt, and the molar ratio of the amount used to the incompletely condensed tandem bench structure of the polymer obtained in step (3) is 10-37:1; The polyether macromonomer described in step (4) is methyl allyl polyoxyethylene ether, isopentanol polyethoxyethylene ether or butanediol monovinyl polyoxyethylene ether with a molecular weight of 2000-5000 g / mol, and the molar ratio of the amount used to the incomplete condensation tandem bench structure of the polymer obtained in step (3) is 10-37:1; The salt removed in step (4) is one or more of cuprous bromide, cupric chloride, cupric bromide, ferric bromide, cuprous chloride, ferric chloride, ferrous bromide or ferrous chloride.
7. A method for repairing concrete cracks in roads, bridges and building structures, characterized in that: The invention is applied with the method for repairing concrete cracks at low temperature as claimed in any one of claims 1 to 6.
8. A concrete crack repairing agent, characterized in that: The invention comprises a low-temperature early strength agent of a tandem stool structure component, wherein the tandem stool structure component low-temperature early strength agent is prepared by ring-opening polymerization of hydroxy POSS and epoxy halide to prepare a tandem stool structure main chain, and then functionally modified by catalysis, substitution-catalysis-copolymerization reaction in sequence to obtain a multimer incomplete condensation tandem stool structure, and then subjected to substitution-ATRP reaction with a halogenated compound, an unsaturated carboxylate small monomer, an unsaturated sulfonic acid small monomer and a polyether macromonomer to obtain the structure; The halogenated compound is 2-bromoisobutyryl bromide or 2-chloroisobutyryl chloride.
Citation Information
Patent Citations
Preparation and application of multifunctional POSS type organosilicon curing agent
CN110452386A
Acetal Group-ContainingHydroxystyrene / POSS-Methacrylate Copolymer andPositive-Type Photoresist Composition Comprising theSame
KR1020040061564A
Cited By
Device and method for actively repairing microcracks on surface of iced water concrete structure
CN120649692A